Evaluation of the Restructuring Policy for the Relocation of Street Vendors (PKL) in Bojonegoro, Indonesia - Enjelina, Adinda Ayu; Suprastiyo, Ahmad; Junadi, Junadi (Universitas Muhammadiyah Gorontalo, 2024)
This study aims to evaluate the effectiveness of the street vendor control policy (PKL) on Street Kartini, Bojonegoro Regency. This policy is designed to create a more orderly, comfortable trade environment and support economic activities without disturbing the aesthetics of the city and public order. This study uses a descriptive qualitative method with a case study approach. Data was collected through in-depth interviews with street vendors, direct observation at the relocation site, and analysis of policy documents and implementation reports from related agencies. The study results show that this policy has successfully achieved several targets in strategic locations such as Street Kartini, where traders reported an increase in customer visits and revenue. However, the effectiveness of this policy is still uneven, especially in other locations such as Street Rajekwesi and Veteran, which are considered less strategic and lack adequate facilities. The main challenges of this policy include traders' resistance to relocation, lack of supporting facilities, and weak supervision of policy implementation. To improve the success of the policy, the government is advised to improve inter-agency coordination, improve facilities at relocation sites, and actively involve traders in the planning and evaluation process. These measures are expected to ensure that the policy provides fair economic benefits for merchants while improving the aesthetics of the city and public order.